Knowledge management in the construction industry a socio-technical perspective - Kazi, Abdul Samad; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This book presents a portfolio of concepts, methods, models, and tools supported by real life case studies from various corners of the globe providing insights into the management of knowledge in the construction industry.
Decision Support Systems and their Application in Construction / Alaa Abdou, Moh'd Radaideh, John Lewis -- A Knowledge Management Portal System for Construction Projects Using Knowledge Map / H. Ping J. Tserng, Yu-Cheng -- An Integrative Knowledge Management System for Environmental-Conscious Construction / Zhen Chen, Stephen C.W. Kong, Heng Li, Qian Xu -- Configurable Environments / William J. O'Brien, Raja R.A. Issa, Zhigang Shen, Haiyan Xie.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 28, 2010).
Keywords: Construction industry -- Management; Knowledge management; Organizational learning; Construction industry -- Information resources management; Electronic books